Occupational noise exposure among airport workers in Malaysia: an ergonomic investigation - Athirah, B.; Nurul Shahida, M. S. (IOP Publishing, 2019)
Occupational noise is defined as a disturbance of sound at a workplace received by a worker's auditory system when they are working. A sustained and prolonged exposure to the noise can cause permanent hearing loss or damage to the worker. According to Occupational Safety and Health Act (OSHA), there is a certain tolerable noise level that can be exposed to the workers at a given time. This study aims to investigate the level of noise produced at the landing area in Sultan Ahmad Shah (SAS) Airport, Kuantan, Malaysia. A comprehensive ergonomic assessment divided into two phases is utilized in order to evaluate the noise exposure of the workers. In Phase I, an initial Ergonomics Risk Assessment is applied to gather the information on the ergonomic risk factors of the noise exposure, while for Phase II, an advanced Ergonomics Risk Assessment is used by monitoring the noise using occupational noise level meter. Thirty workers from the landing area which consists of the ground handlers were included as the subjects for this study. The value of noise exposure is measured while the workers perform their job. Results suggested that (a) the workers are aware of the noise exposure as per results shown in initial Ergonomics Risk Assessment in Phase I, and (b) the workers were exposed to high level of noise as suggested by OSHA (> 100 dBA at 2 hours exposure). With the suggested findings, the management of SAS Airport needs to create sufficient awareness to emphasize the usage of hearing protection devices in the workplace.